Aplikasi dan Evaluasi Paradigma Integrasi - Interkoneksi dalam Pendidikan Pengajaran - Bukhari, Akh. (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This research tried to describe the concept of integrative-interconnection of teaching and learning at IAIN Samarinda. The approach of integrative-interconnection is a kind of approach which uses a point of view and/or the united analysis method. The lecturing lessons, which enable to be integrated, should be discussed to find the similarity and the usefulness of them, so that they could be more comprehensive and more contextual. The application of this paradigm has been described that it has some obstacles when it was evaluated. The findings of this research can be a reference for a further similar research about concept of integrative-interconnection in the future.